Effectiveness of theory-based intervention using social media to reduce urinary incontinence among postpartum women in Hebron city hospitals - Mesk, Zeenat M.S. (2020)
Urinary incontinence (UI) is a common condition and closely related to childbirth. Women who give birth are at higher risk of developing UI and prefer to follow a pelvic floor muscle exercise (PFME) program to sustain or strengthen pelvic floor muscle weakness and UI in prenatal and later life compared to women who have not given birth to a baby. Pelvic floor muscles exercises are considered by the International Continence Society as the first line of treatment for UI. It has an important role to play in UI prevention and treatment, and PFMEs regular practice is a key factor in their efficacy. The aim of this study was to develop, implement and evaluate a theory-based intervention using social media to reduce UI among postpartum which was conducted in Hebron city hospitals in Palestine. A randomized controlled trial which is two-arm with a sample size of 110 participants was used to collect data in Al-Ahli outpatient clinic in Hebron City from the admitted postpartum women. The participants were grouped randomly into two groups: first group is a control and the second group is intervention who were follow up at 3 and 6 months. The primary outcome of this study was severity of urinary incontinence. Self-efficacy for exercise, adherence to exercises, perceive benefit, perceive severity, and perceive barrier were the secondary outcomes. Participants in the intervention group received training and education about pelvic floor muscles exercises through WhatsApp follow the concepts of health belief model A total of 110 participants were involved in this study: 55 in the intervention group and 55 in the control group. The results of the Chi-Square test indicated that at baseline, there were no significant differences between the intervention and control groups by age, number of deliveries, weight, and height, and educational level, type of delivery and medical conditions. The statistics also showed that there were no statistically significant differences between the two groups at baseline regarding the severity of UI and the practice of PFMEs and there were also no differences in perceived barriers, perceived benefits, self-efficacy and cues to action to practise PFMEs. After the intervention, at 3 months and 6 months follow-up, there were significant differences between the intervention and control groups regarding the practice of PFMEs. There were also within-group differences in the intervention group. Friedman’s analysis of variance showed that there was a significant difference in respect of the exercise adherence rating scale in the intervention group at baseline, at 3 months and post 6 months. In the intervention group at baseline the mean rank of the International Consultation on Incontinence Questionnaire Short Form (ICIQ) was 3.00, whereas at 3 months it decreased to 1.96 and at 6 months it fell further to 1.04, which indicated that there was a decrease in the severity of UI after the intervention. The provision of theory-based education delivered through social media is a feasible and effective way of increasing the practice of PFMEs, and can lead to a decrease in the severity of UI.